Código Lingüístico y no Lingüístico - Solano Obeso, Mariela Rosmery (2018)
The session entitled use of the linguistic and non-linguistic code, was developed in the area of communication taking into account the competence of comprehension of texts, the performance of identifying and using the meaning of some signals and linguistic and nonlinguistic code was achieved._x000D_ Nowadays we live surrounded by codes and it is necessary to know and interpret them in an appropriate way, for a correct practice of these, therefore activities were developed to know the linguistic and non-linguistic codes to use them correctly and interpret them._x000D_ In the course of the session, motivating and challenging activities were implemented that encouraged the achievement of their reading skills and abilities._x000D_ The pedagogical processes such as the motivation, the exploration of knowledge, problematization, management and accompaniment, evaluation and transfer in the didactic processes of the area were considered in the execution before, during and after the text._x000D_ The constant and active participation of the students was promoted individually and as a group, from which they were able to identify their new learning with which they will obtain new ones. The strategies executed were in accordance with the interests and needs they showed.